Ethnomathematics at javanese traditional food market - Lola Febriyanty; Amanda Syahri Nasution (Jurnal Pijar Mipa, 2022)
This study aims to describe the ethnomathematics of traditional Javanese food or snack in terms of geometry topics. We also study the ethnomathematics profit price sales of typical Javanese snacks  for the linear equation systems topic. This research is a qualitative descriptive study. This research was conducted in Medan Sinembah village specified for market snacks. Data were obtained in interviews, observations, and documentation. The results showed that typical Javanese market snacks' mathematical concepts include two-dimensional geometry, three-dimensional geometry, and linear equations. Ethnomathematics activities in typical Javanese market snacks are counting activities, measuring activities, and geometric aspects.